Respuesta :

Answer:

29

Step-by-step explanation:

[tex] \sin \: (x - 3) = \cos \: (2x + 6) \\ \\ \sin \: (x - 3) = \sin \bigg \{ \frac{\pi}{2} - \: (2x + 6) \bigg\} \\ \\ x - 3 = \frac{ \pi}{2} - \: (2x + 6) \\ \\ x - 3 + 2x + 6 = \frac{\pi}{2} \\ \\ 3x + 3 = \frac{\pi}{2} \\ \\ 3x = \frac{\pi}{2} - 3 \\ \\ x = \frac{\frac{\pi}{2} - 3 }{3} \\ \\ x = \frac{\pi}{2 \times 3} - \frac{3}{3} \\ \\ x = \frac{\pi}{6} - \frac{3}{3} \\ \\ x = 30 - 1 \\ \\ \huge \red{ \boxed{x = 29}} \\ [/tex]

ACCESS MORE